Long-Term Follow-Up of the Fellow Eye in Patients Undergoing Surgery on One Eye for Treating Myopic Traction Maculopathy. (12th July 2016) - Xia, Hui-Juan; Wang, Wei-Jun; Chen, Feng'E; Wu, Ying; Cai, Zhen-Yuan; Chen, Wei; Yu, Su-Qin; Fan, Ying
Abstract : Objective . To observe the fellow eye in patients undergoing surgery on one eye for treating myopic traction maculopathy. Methods . 99 fellow eyes of consecutive patients who underwent unilateral surgery to treat MTM were retrospectively evaluated. All patients underwent thorough ophthalmologic examinations, including age, gender, duration of follow-up, refraction, axial length, intraocular pressure, lens status, presence/absence of a staphyloma, and best-corrected visual acuity (BCVA). Fundus photographs and SD-OCT images were obtained. When feasible, MP-1 microperimetry was performed to evaluate macular sensitivity and fixation stability. Results . At an average follow-up time of 24.7 months, 7% fellow eyes exhibited partial or complete MTM resolution, 68% stabilized, and 25% exhibited progression of MTM. Of the 38 eyes with "normal" macular structure on initial examination, 11% exhibited disease progression. The difference in progression rates in Groups 2, 3, and 4 was statistically significant. Refraction, axial length, the frequency of a posterior staphyloma, chorioretinal atrophy, initial BCVA, final BCVA, and retinal sensitivity all differed significantly among Groups 1–4. Conclusions . Long axial length, chorioretinal atrophy, a posterior staphyloma, and anterior traction contribute to MTM development. Patients with high myopia and unilateral MTM require regular OCT monitoring of the fellow eye to assess progression to myopic pre-MTM. For cases exhibiting one or more potential risk factors, early surgical intervention may maximize the visual outcomes.